The Practice of Forward Prospecting of Adverse Geology Applied to Hard Rock TBM Tunnel Construction: The Case of the Songhua River Water Conveyance Project in the Middle of Jilin Province. (February 2018) - Li, Shucai; Nie, Lichao; Liu, Bin
Abstract: An increasing number of tunnels are being constructed with tunnel-boring machines (TBMs) due to the increased efficiency and shorter completion time resulting from their use. However, when a TBM encounters adverse geological conditions in the course of tunnel construction (e.g., karst caves, faults, or fractured zones), disasters such as water and mud inrush, collapse, or machine blockage may result, and may severely imperil construction safety. Therefore, the advance detection of adverse geology and water-bearing conditions in front of the tunnel face is of great importance. This paper uses the TBM tunneling of the water conveyance project from Songhua River as a case study in order to propose a comprehensive forward geological prospecting technical system that is suitable for TBM tunnel construction under complicated geological conditions. By combining geological analysis with forward geological prospecting using a three-dimensional (3D) induced polarization method and a 3D seismic method, a comprehensive forward geological prospecting technical system can accurately forecast water inrush geo-hazards or faults in front of the TBM tunnel face. In this way, disasters such as water and mud inrush, collapse, or machine blockage can be avoided. This prospecting technical system also has reference value for carrying out the forward prospecting of adverse geology for potential TBM tunneling and for ensuring that a TBM can work efficiently.